Penentuan Kualitas Produk melalui Pendekatan Fuzzy-Mamdani serta Penerapan AHP untuk Optimasi Produksi Tepung Tapioka - Gea, Carlo Raphael; Aviandra, Anisa Putri; Sadid, Achmad; Bratawijaya, Intan Armelianti (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The manufacturing industry plays a crucial role in the process of transforming raw materials into finished products. Quality is an aspect that influences the level of consumer purchases. This study aims to examine the fineness of flour and the criteria that impact the selection of alternatives in the optimization of the production process. The Mamdani Fuzzy Logic approach is used to evaluate the fineness of flour based on parameters affecting product quality, namely 14% moisture content, drying time of 5 hours, and drying temperature of 55°C. The processing of input variables involves 27 fuzzy rules and utilizes the defuzzification process, resulting in an output of 15 µm. The application of the AHP method aims to identify weight values to determine priorities for the selection of alternative decisions. The mapping of weight values produces a Consistency Ratio of 0.69959 (Temperature and Humidity), 0.66050 (Quality Consistency), 0.50211 (New Drying Technology) which becomes the selected alternatives. The results of the study indicate that the combination of both methods significantly influences the fineness of flour and production optimization at CV. Tepung Tapioka XYZ.